Workers' compensation law - Jasper, Margaret C. (New York : Oceana, 2008)
'Discusses common elements of a workers' compensation program, including filing of a claim; receipt of benefits. Provides overview of the Federal program for disabled non-military federal employees; Longshore & Harbor Workers' Compensation Program; Black Lung Benefits Program; Energy Employees' Occupational Illness Compensation Program; Federal Employment Liability Act; Merchant Marine Act; Veterans Disability programs; Social Security Disability Insurance program'--Provided by publisher
Overview of workers' compensation -- Filing the workers' compensation claim -- Workers' compensation benefits -- The federal employees' compensation program -- The longshore and harbor workers' compensation -- The black lung benefits program -- The energy employees' occupational illness compensation program -- Additional federal disability programs
Includes bibliographical references (p. 269)
Keywords: Workers' compensation -- Law and legislation -- United States -- Popular works